Current Approaches for Investigating and Predicting Cytochrome P450 3A4-Ligand Interactions - Sevrioukova, Irina F. (Adv Exp Med Biol, 2015)
Cytochrome P450 3A4 (CYP3A4) is the major and most important drug-metabolizing enzyme in humans that oxidizes and clears over a half of all administered pharmaceuticals. This is possible because CYP3A4 is promiscuous with respect to substrate binding and has the ability to catalyze diverse oxidative chemistries in addition to traditional hydroxylation reactions. Furthermore, CYP3A4 binds and oxidizes a number of substrates in a cooperative manner and can be both induced and inactivated by drugs. In vivo, CYP3A4 inhibition could lead to undesired drug-drug interactions and drug toxicity, a major reason for late-stage clinical failures and withdrawal of marketed pharmaceuticals. Owing to its central role in drug metabolism, many aspects of CYP3A4 catalysis have been extensively studied by various techniques. Here, we give an overview of experimental and theoretical methods currently used for investigation and prediction of CYP3A4-ligand interactions, a defining factor in drug metabolism, with an emphasis on the problems addressed and conclusions derived from the studies.